PENGARUH PENGGUNAAN ARTIFICAL INTELLEGENCE (AI) CHATGPT TERHADAP KUALITAS PRESENTASI MAHASISWA FKIP PPKN PALEMBANG UNIVERSITAS SRIWIJAYA - Irma, Ade; El Faisal, Emil (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of Artificial Intelligence (AI) in the era of the Industrial Revolution 4.0 has significantly transformed higher education learning processes. One AI-based tool that has been increasingly utilized by students is ChatGPT, particularly as academic support in preparing presentations. This study aims to analyze the effect of using Artificial Intelligence (AI) ChatGPT on the presentation quality of students in the Civic Education (PPKn) Study Program, Faculty of Teacher Training and Education, Universitas Sriwijaya Palembang. This research employed a quantitative approach with an ex post facto design. The population consisted of 110 students, with 52 students selected as samples using proportional random sampling. Data were collected through a Likert-scale questionnaire and analyzed using normality tests, linearity tests, simple linear regression, correlation analysis, t-tests, and F-tests with the assistance of SPSS. The results indicate that the use of ChatGPT has a positive and significant effect on students’ presentation quality, with a significance value of 0.000 (< 0.05) and a coefficient of determination of 29.7%. These findings suggest that ChatGPT contributes to better material organization, improved content mastery, and increased student confidence during presentations. However, its use should be conducted wisely to avoid excessive dependence that may hinder creativity and critical thinking skills.